Growth and yield of cherry tomato (Lycopersicum esculentum Mill. var cerasiforme) as influenced by water stress grown under different greenhouse systems - Hasbullah, Norfahida; Sakimin, Siti Zaharah; Dahlan, Nofri Yenita; Ramlan, Mohd Fauzi; Baghdadi, Ali (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Cherry tomato is very popular among consumers because of its high nutritional values. Growth, yield and quality of cherry tomatoes can be easily affected by the amount of water received by the plant as well as by the growing environment. Fruits show a symptom of sunburn if it is grown under too hot temperature in open field planting or under the greenhouse. The plants also required a lot of water for them to grow well and will be adversely affected by water stress (WS). The experiment was conducted to determine the effect of water stress on growth, yield and water use efficiency (WUE) of cherry tomato grown under different greenhouse systems. Cherry tomato plants were subjected to three levels of water stress treatments and were placed under smart greenhouse system (SGS) and conventional greenhouse system (CGS). Plant height and leaf area (LA) data were recorded at 30, 60 and 90 days after transplanting (DAT). While the total yield of cherry tomato was only recorded at day 90 DAT. The result of the study shows that at 30 DAT, plant height of 100% of soil field capacity treatment was significantly higher than other WS for both SGS and CGS. At 90 DAT, there was no significant differential effect on plant height for all WS treatment for SGS, but for CGS, 100% of soil field capacity treatment was significantly lower than other WS treatments. There was no significant difference between mild water stress and severe water stress treatment for CGS at 90 DAT. Significantly higher LA and a total number of fruits were recorded for 100% of soil field capacity treatment than other especially at 60 and 90 DAT for both SGS and CGS. Overall, evidence recorded from this study proves that plant height, leaf area and a total number of fruits were performed better under 100% of soil field capacity and SGS. The microenvironment of greenhouse must suit the requirement of the plant for them to grow well and yield can be optimised.